Structure Elucidation and Analgesic Activity of Separated Active Compounds from the Methanolic Extract of Solanum torvum - Bhusan Paul, Satya; Datta Choudhury, Manabendra; Choudhury, Ratna; De, Biplab (Asian Journal of Chemistry, 2010)
Methanolic extract of fruits of Solanum torvum Swartz was subjected for column chromatography taking ethyl acetate as mobile phase. The separated and purified chemical constituents and crude extract were tested for their analgesic activity by acetic acid induced writhing method. The structures of therapeutically active constituents were elucidated by spectral analysis and they were steroidal glycosides.